2019
DOI: 10.3390/su11061715
|View full text |Cite
|
Sign up to set email alerts
|

The Romanian Family Businesses Philosophy for Performance and Sustainability

Abstract: Family businesses represent a large segment of private companies and contribute greatly to economic growth. In this context, the objectives of this paper are to identify the characteristics of Romanian family businesses, starting from their involvement and governance mechanisms, and also to investigate if these specific items allow them to act towards creating sustainable businesses. In order to achieve these objectives, we have used qualitative and quantitative research, consisting of two phases: (a) we have … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(26 citation statements)
references
References 66 publications
(89 reference statements)
1
13
0
1
Order By: Relevance
“…The importance of culture has been studied previously [59]. In particular, Hategan et al (2019) [71] analyzed the effect of culture on sustainability in family businesses. This result shows how one aspect of structural capital affects financial performance, coinciding with Xu et al (2018) [15].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The importance of culture has been studied previously [59]. In particular, Hategan et al (2019) [71] analyzed the effect of culture on sustainability in family businesses. This result shows how one aspect of structural capital affects financial performance, coinciding with Xu et al (2018) [15].…”
Section: Discussionmentioning
confidence: 99%
“…First, local culture reduces transaction costs, but to translate this reduction of cost into value for clients, it is necessary to have an efficient organizational system [70] and good leadership, which are usually not present in SSBs [71]. This effect is therefore limited.…”
Section: Culture Leadership and Sustainabilitymentioning
confidence: 99%
“…: family members) resulted in lower earnings. Hategan et al (2019) examine the relationship between family firms and social responsibility awareness using a Romanian sample. They found that Romanian family firms have greater attention on the current changes in business environment and prepared an internal process strategy to response this changes.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The key performance indicators are the family passion for the business, family governance policy, powerful emotional attachment of the family to the company, willingness to transfer the business to the future generation, innovative tools to continuously perform the family business brand, family experience, family influence, and recognition [1,14]. A family business is characterized not necessarily by its size or by the percentage of stake owned, but most importantly, by the voting rights a family has over the business.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Family businesses account for a great number of private companies, and are perceived as the backbone of the world's economy and as sustainable business models [1]. The phenomena of globalization and hyper-competition have drawn scholars' attention regarding family businesses' fast decision-making processes, which affect their business performance [2].…”
Section: Introductionmentioning
confidence: 99%